2013
DOI: 10.1021/am402855v
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Thiol Functional Linker Mediated Sustainable Anti-Biofouling Ultrafiltration Nanocomposite Comprising a Silver Nanoparticles and Poly(vinylidene fluoride) Membrane

Abstract: We develop sustainable anti-biofouling ultrafiltration membrane nanocomposites by covalently immobilizing silver nanoparticles (AgNPs) onto poly(vinylidene fluoride) (PVDF) membrane mediated by a thiol-end functional amphiphilic block copolymer linker. Field emission scanning electron microscopy (FE-SEM) and energy-dispersive X-ray spectroscopy (EDXS) measurements reveal that the AgNPs are highly bound and dispersed to the PVDF membrane due to the strong affinity of the AgNPs with the thiol-modified block copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 37 publications
(49 reference statements)
0
39
0
Order By: Relevance
“…The stable and strong bond between the AgNPs and the membrane is important for ensuring the maintenance of anti-biofouling performance for high-efficient and eco-friendly membrane system 34 . The release rate of silver from the AgNPs grafted membrane was examined in both static and filtration experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The stable and strong bond between the AgNPs and the membrane is important for ensuring the maintenance of anti-biofouling performance for high-efficient and eco-friendly membrane system 34 . The release rate of silver from the AgNPs grafted membrane was examined in both static and filtration experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Different properties can be obtained by tailoring membrane with varying blend composition to obtain desired membrane structure. For this purpose, inorganic nano-materials are used as nanofillers to incorporate into polymer matrices for enhanced membrane performance [82,110,111]. Among these methods, surface grafting and surface coating are commonly used to enhance anti-fouling property and imparting hydrophilic character to membrane.…”
Section: Modification Of Polymeric Membranesmentioning
confidence: 99%
“…Moreover, the positive charges should be maintained during membrane operation. Previously, we reported a technique to tightly anchor various functional materials onto the UF/MF membrane surface using hydrophilic-hydrophobic phase recognition during a membrane fabrication process, resulting in reduced biofouling [22] and the removal of hazardous materials such as heavy metal ions [23] and endocrine disrupting chemicals (EDCs) [24]. Furthermore, we showed that these modified membranes maintained their desired properties through excellent binding stability.…”
Section: Introductionmentioning
confidence: 99%